Παράγοντες υιοθέτησης καταλληλότερου συστήματος Επαυξητικής και Εναλλακτικής Επικοινωνίας από άτομο με Εγκεφαλική Παράλυση - Μιχαήλ, Σουζάνα (My University, 2023)
This thesis presents a case study of a person with a ‘Cerebral Palsy’ (CP) birth defect. The purpose of this study is to investigate the views of a person with complex communication needs (CCN) and the views of the subject’s carer, regarding the ‘Augmentative and Alternative Communication’ (AAC) systems. The acceptance or rejection factors of these systems by the subject, are also discussed in this thesis, following the communicative interactions of the subject with their carer in order to find the most suitable ‘Augmentative and Alternative Communication’ system, for each individual subject. As part of the research, structured interviews were conducted by three persons themselves directly involved; the woman who was selected for the case study (the subject), her mother and her personal helper. After careful consideration of the research questions, relevant bibliographic references were examined, and the analysis of all data were carried out using the ‘Thematic Analysis’ method. The conclusions obtained by this research, indicate the most important acceptance or rejection factors of a system. They are as follows, its convenience and simplicity of use; the amount of time required to train the subject in using the system and the extent of mental and physical support provided by the people in the subject’s living environment. Moreover, other acceptance or rejection factors include a need to utilize the advances of new technology and finally as to how far there is personalisation of the system that will fend for the particular needs of each subject. The research also shows that it is important that the caregivers that work alongside the subject and are the most familiar to the subject’s communicative needs, watch and attend the various testing of these systems, performed by the subject, so that they are able to know to a satisfactory level, the potential of each system and the difficulties that the subject may come across. Both, to keep supporting the subject as well as to keep the relevant specialist informed.
Keywords: Επαυξητική και Εναλλακτική Επικοινωνία; Εγκεφαλική Παράλυση; Παράγοντες αποδοχής; Παράγοντες απόρριψης συστημάτων; Πολύπλοκες Επικοινωνιακές Ανάγκες; Augmentative and Alternative Communication; Cerebral Palsy; acceptance or rejection factors; complex communication needs